Electron-rich, Nitrido-bridged Ruthenium Complexes - Glueer, Arne; Askevold, Bjorn; Schluschass, Bastian; Heinemann, Frank Wilhelm; Schneider, Sven (Zeitschrift für Anorganische und Allgemeine Chemie, 2015)
Terminal Ru-IV nitride [RuNN(CH2CH2PtBu2)(2)] (1) and [RuClN(CH2CH2PtBu2)(2)] (2a) form an equilibrium with bridging nitride [(tBu(2)PCH(2)CH(2))(2)N Ru(mu-N) RuClN(CH2CH2PtBu2)(2)] (3a). While 3a could only be spectroscopically characterized yet not isolated, the reaction of the divinylamido chloro complex [RuClN(CHCHPtBu2)(2)] (2b) with half an equivalent azide directly gave the analogous bridging nitride [(tBu(2)PCHCH)(2)N Ru(mu N) RuClN(CHCHPtBu2)(2)] (3b), which was isolated and fully characterized.
Keywords: Nitride; Ruthenium; Bridging ligands; Pincer ligand